Evolution of Management Theory within 20 Century: A Systemic Overview of Paradigm Shifts in Management - Khorasani, Sasan Torabzadeh; Almasifard, Maryam (International Review of Management and Marketing, 2017)
Significant progress in civilization of human being has been made over 20century. Advance technology; globalization and revolution of communication are the main outcomes of this development. However, it is obvious that these achievements have been significantly influenced by evolution of management theories. The paradigm shift from classical management to modern management can be clustered into several phases. This paper presents an overview of evolution of management theory within 20 century, and provides an analogy of the notion of Kuhn's scientific paradigm in terms of management theory evolution. Moreover, the Intersections of management with other sciences or Medici effect that have been occurred in this area (Johansson, 2004) will be discussed in this article. Keywords: Management Theory, Paradigm shift, Kuhn, Medici effect JEL Classification: B15